2017
DOI: 10.1111/febs.14357
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterization of wild‐type and mutant human thioredoxin glutathione reductase defines its reaction and regulatory mechanisms

Abstract: EC numbers: 1.8.1.9; 1.8.1.B1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…As a corollary, it can be concluded that the slope observed at the reactivating segment does not correspond to an authentic steady-state velocity. This point must be stressed, because, in some works dealing with the atypical kinetic behavior of TGR [ 11 , 16 , 37 ], the maximal slope in a full time progress curve of GSSG reductase activity has been mistakenly noted as a true steady-state velocity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a corollary, it can be concluded that the slope observed at the reactivating segment does not correspond to an authentic steady-state velocity. This point must be stressed, because, in some works dealing with the atypical kinetic behavior of TGR [ 11 , 16 , 37 ], the maximal slope in a full time progress curve of GSSG reductase activity has been mistakenly noted as a true steady-state velocity.…”
Section: Discussionmentioning
confidence: 99%
“…A comment concerning a recently published paper dealing with recombinant human TGR [ 11 ]. In such work, the effect of high concentrations of GSSG on enzyme activity was tested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations